2020
DOI: 10.26603/ijspt20200001
|View full text |Cite
|
Sign up to set email alerts
|

Post-Operative Sport Participation and Satisfaction With Return to Activity After Matrix-Induced Autologous Chondrocyte Implantation in the Knee

Abstract: Background: Returning to a satisfactory activity level is expected by patients after cartilage repair, and may define overall surgical success.Purpose: To investigate: 1) the level and improvement in activity in patients at two years after matrix-induced autologous chondrocyte implantation (MACI), 2) what factors are associated with post-operative (and improvement in) activity level, and 3) whether patients are satisfied with their ability to participate in recreational and/or sporting activities. Study Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It has been shown that addressing simultaneously both, cartilage lesion and concomitant injury, does not negatively affect the return-to-play rate. 85 In the presence of a concomitant meniscus tear it is crucial to suture and refixate the tissue where possible, as a partial or full meniscectomy is known to be a contributor to progression of osteoarthritis and negatively affects the healing potential of the cartilage lesion. 3 While a debridement of a meniscus lesion might lead to an earlier RTP, its mid-and long-term effects are less favorable and should therefore be avoided if possible.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that addressing simultaneously both, cartilage lesion and concomitant injury, does not negatively affect the return-to-play rate. 85 In the presence of a concomitant meniscus tear it is crucial to suture and refixate the tissue where possible, as a partial or full meniscectomy is known to be a contributor to progression of osteoarthritis and negatively affects the healing potential of the cartilage lesion. 3 While a debridement of a meniscus lesion might lead to an earlier RTP, its mid-and long-term effects are less favorable and should therefore be avoided if possible.…”
Section: Discussionmentioning
confidence: 99%
“…ACI is indicated for larger, grade 3 to 4 lesions, yielding significant improvements for patients with lesions as large as 14 cm 2 and 12 mm deep into subchondral bone 2 . Significant improvements in function and pain following ACI are evident at short-term (85% return to recreational activities, 66% return to sport at 2 years) and long-term follow-up (stable clinical improvements with a 10% failure rate at 11 years) 39,40 . However, patient expectations must be managed as ACI requires 2 surgeries and 6 weeks non–weight-bearing postoperatively 2 .…”
Section: Operative Managementmentioning
confidence: 99%
“…2). In a prospective cohort study of 150 patients who underwent matrix-induced autologous chondrocyte implantation with 2-year follow-up, 85% and 66% of patients were satisfied with their ability to return to recreational activities and sports, respectively 49. In a separate study of 97 patients with interval follow-up at 1, 2, and 5 years, satisfaction with sports was achieved in 55.7%, 73.2%, and 68.5% of patients, respectively 50.…”
Section: Kneementioning
confidence: 99%